Tanypus urszulae, a new Tanypodinae (Diptera: Chironomidae) from the Neotropical Region - Silva, Fabio Laurindo Da; Oliveira, Caroline Silva Neubern De (Zootaxa, 2016)
A new species of Tanypus Meigen, T. urszulae sp. nov. from Brazil, is described and figured as adult male, pupa and larva. Additionally, the generic diagnosis for the larva is emended.